2016
DOI: 10.1021/acs.jafc.6b02068
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of BSA–Green Tea Polyphenols–Chitosan Nanoparticles and Their Role in Radioprotection: A Molecular and Biochemical Approach

Abstract: Normal tissue damage from ionizing radiation during radiotherapy is a major concern in cancer treatment. Tea polyphenols (TPs) have been shown to reduce radiation-induced damage in multiple studies, but their pharmacological application is still limited due to poor bioavailability. The present study was aimed at to increase the TPs bioavailability by nanoformulation by using BSA as the matrix and chitosan as the external shell. Encapsulated TPs nanoparticles were spherical in size and promoted TPs stability in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 33 publications
0
24
1
1
Order By: Relevance
“…Both EGCG ovalbumin−dextran conjugate nanoparticle and chitosan coated BSA–EGCG nanoparticle showed significantly higher apparent permeability coefficient compared to free EGCG in solution, resulting in an improvement of the EGCG absorption [ 46 , 47 ]. The radioprotection effect of chitosan coated BSA–polyphenols nanoparticles by oral administration in mice was significantly higher than that of free polyphenols [ 48 ].…”
Section: Improving the Bioavailability Of Catechinsmentioning
confidence: 99%
“…Both EGCG ovalbumin−dextran conjugate nanoparticle and chitosan coated BSA–EGCG nanoparticle showed significantly higher apparent permeability coefficient compared to free EGCG in solution, resulting in an improvement of the EGCG absorption [ 46 , 47 ]. The radioprotection effect of chitosan coated BSA–polyphenols nanoparticles by oral administration in mice was significantly higher than that of free polyphenols [ 48 ].…”
Section: Improving the Bioavailability Of Catechinsmentioning
confidence: 99%
“…Similar results was also reported. 10 This is mainly attributed to that DLS data were obtained in solution where nanoparticles were fully hydrated, while TEM images were got in a dry state on carboncoated copper grid.…”
Section: Ca Conjugation Optimizationmentioning
confidence: 99%
“…The bioabsorption of EGCG was less than 1.1% aer oral administration. 9,10 Recent studies showed that the absorption of EGCG was enhanced when delivered in nanoparticles. The result was mainly attributed to the stabilization of EGCG in nanoparticles rather than the effect of nanoparticles on intestinal transport or on efflux proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the bioavailability of tea polyphenols (TPs) was improved by chitosan and bovine serum albumin (BSA) nanoformulation in mice. Animals were fed by nanoparticles for 3 days before irradiation exposure leading to enhancement of DNA stability via the reduction of oxidative damage [141]. Similarly, silver nanoparticles in combination with glycyrrhizic acid protected Swiss albino mice against ionising radiation, by decrease of DNA strand breaks formation and increase in their repairs [142].…”
Section: Plant Bioactive Compounds Formulated As Nanoparticlesmentioning
confidence: 99%